GAMBUT LESTARI : AWARENESS SOLUTIONS FOR THE CRISIS OF PEATLAND - Alya Lihan Eltofani; Fauzan Ishaq; Rani Melani Aldina Wijaya (Faculty of Social and Political Sciences Universitas Kristen Indonesia, 2020)
Peatland reserves one-third of the world's carbon storage. In 1 year it is evaluated that the peatland absorbs and contains 22.5 - 43.5 gigatonnes of carbon, which is proportionate to the outflows of 17-33 billion cars. Looking back on 2015, more than 50% or 2 million hectares of peatlands were burned down causing 220 trillion rupiah loss, victims suffering from respiratory diseases, disconnection of transportation networks and threats to biodiversity. The aim of this paper is to know the strategies used to increase awareness of peatlands and these discoveries appearing the sort of data and information that required prioritization to educate and advance such awareness. The method used for this paper is divided into two for the project planning and data collection instrument. For the data collection instrument, we used the data from third parties. The project planning that we conclude are including gambutlestari.com, pilot, share information, training & education, signing the petition, and donation. Our project planning is encouraging the participation of people to increase the preventive action towards peatlands damage and indirectly fixed the peatlands damage that previously happened. In conclusion, it is a developed system to create the discussion for an educational training program. Hence, each party can embrace in communicating and advancing awareness on the peatland issue. Achieving our goal to be able to increase awareness of peatlands in Indonesia, we provide a one-stop service called “Push-Sustainable Peatlands” which can be accessed easily by everyone.